P09.41 Chlamydia trachomatis screening among preterm births in brazil: an experience from a university hospital. (13th September 2015) - Schmidt, R; Muniz, RR; Cola, E; Stauffert, D; Silveira, MF; Miranda, AE
Abstract : Background: Premature birth (PPT) is a major determinant of neonatal morbimortality with adverse consequences for health. The causes are multifactorial, with intrauterine infection probably explains most of these outcomes. It is believed that infection with Chlamydia trachomatis (CT) is also involved in PPT and premature rupture of membranes. Our goal was to study the prevalence of CT in pregnant women and associated factors related to cases of PPT attended in an University Hospital in Vitoria, Brazil. Methods: A cross-sectional study performed among parturient who have preterm birth in a University Hospital from June 2012 to August 2013. Participants answered a questionnaire including demographic, behavioural, and clinical data. A sample of urine was collected and screened for CT using polymerase chain reaction. Results: The prevalence of PPT in the hospital during the period of the study was 26%. A total of 378 cases of PPT were registered, among them 323 women participated and were tested for CT, forty-five (13.9%) had a positive result. 31.6% was up to 24 years old and women infected by CT were younger than the others (p = 0.022). A total of 76.2% were married/living together, and CT was more frequent among the single ones (p = 0.018); 16.7% of women had their first sexual activity under 14 years old. The causes of prematurity were maternal-fetal in 40.9%, rupture of the membranes in 29.7% and premature labour in 29.4%. In multivariate analysis, being married was a protective factor for infection [OR = 12:48 (95% CI: 0.24–0.97)]. None of the other characteristics were associated with CT infection. Conclusions: This study shows a high prevalence of preterm birth and CT infection among parturient who have preterm birth. This high prevalence increases the need for defining screening strategies and assistance during the prenatal period. Disclosure of interest statement: There is no conflict of interest